A high‐resolution record of Greenland mass balance. Issue 13 (9th July 2016) - McMillan, Malcolm; Leeson, Amber; Shepherd, Andrew; Briggs, Kate; Armitage, Thomas W. K.; Hogg, Anna; Kuipers Munneke, Peter; van den Broeke, Michiel; Noël, Brice; van de Berg, Willem Jan; Ligtenberg, Stefan; Horwath, Martin; et al.
Abstract: We map recent Greenland Ice Sheet elevation change at high spatial (5 km) and temporal (monthly) resolution using CryoSat‐2 altimetry. After correcting for the impact of changing snowpack properties associated with unprecedented surface melting in 2012, we find good agreement (3 cm/yr bias) with airborne measurements. With the aid of regional climate and firn modeling, we compute high spatial and temporal resolution records of Greenland mass evolution, which correlate ( R  = 0.96) with monthly satellite gravimetry and reveal glacier dynamic imbalance. During 2011–2014, Greenland mass loss averaged 269 ± 51 Gt/yr. Atmospherically driven losses were widespread, with surface melt variability driving large fluctuations in the annual mass deficit. Terminus regions of five dynamically thinning glaciers, which constitute less than 1% of Greenland's area, contributed more than 12% of the net ice loss. This high‐resolution record demonstrates that mass deficits extending over small spatial and temporal scales have made a relatively large contribution to recent ice sheet imbalance. Key Points: Greenland contributed 0.74 ± 0.14 mm/yr to global mean sea level between 2011 and 2014 Small‐scale mass deficits have made a relatively large contribution to recent ice loss High‐resolution radar altimetry can map Greenland mass balance at fine spatial and temporal resolution